Functional Dynamics of the Gut Microbiome in Elderly People during Probiotic Consumption - Emiley A. Eloe-Fadrosh (American Society for Microbiology, 2015)
ABSTRACT A mechanistic understanding of the purported health benefits conferred by consumption of probiotic bacteria has been limited by our knowledge of the resident gut microbiota and its interaction with the host. Here, we detail the impact of a single-organism probiotic, Lactobacillus rhamnosus GG ATCC 53103 (LGG), on the structure and functional dynamics (gene expression) of the gut microbiota in a study of 12 healthy individuals, 65 to 80 years old. The analysis revealed that while the overall community composition was stable as assessed by 16S rRNA profiling, the transcriptional response of the gut microbiota was modulated by probiotic treatment. Comparison of transcriptional profiles based on taxonomic composition yielded three distinct transcriptome groups that displayed considerable differences in functional dynamics. The transcriptional profile of LGG in vivo was remarkably concordant across study subjects despite the considerable interindividual nature of the gut microbiota. However, we identified genes involved in flagellar motility, chemotaxis, and adhesion from Bifidobacterium and the dominant butyrate producers Roseburia and Eubacterium whose expression was increased during probiotic consumption, suggesting that LGG may promote interactions between key constituents of the microbiota and the host epithelium. These results provide evidence for the discrete functional effects imparted by a specific single-organism probiotic and challenge the prevailing notion that probiotics substantially modify the resident microbiota within nondiseased individuals in an appreciable fashion. IMPORTANCE Probiotic bacteria have been used for over a century to promote digestive health. Many individuals report that probiotics alleviate a number of digestive issues, yet little evidence links how probiotic microbes influence human health. Here, we show how the resident microbes that inhabit the healthy human gut respond to a probiotic. The well-studied probiotic Lactobacillus rhamnosus GG ATCC 53103 (LGG) was administered in a clinical trial, and a suite of measurements of the resident microbes were taken to evaluate potential changes over the course of probiotic consumption. We found that LGG transiently enriches for functions to potentially promote anti-inflammatory pathways in the resident microbes.